Comparison of potential plasma biomarkers in Alzheimer’s disease and neurodegenerative dementias in Pakistani population - Faraz Ahmed, Tehniat; Imtiaz, Fauzia; Zaman, Uzma; Ahmed, Affan; Shahbaz, Naila (Journal of the Pakistan Medical Association, 2023)
This study aimed to compare the mean plasma levels of Amyloid B42, Phosphorylated Tau and Neurofilament Light chain in patients diagnosed with Alzheimer’s Clinical Syndrome (ACS), and other neurodegenerative dementias to find affordable and less-invasive means of diagnosing Alzheimer’s disease (AD) early in its course. Blood samples of 36 subjects presenting with cognitive decline to the neurology OPDs of Dow and Civil hospitals, Karachi, were centrifuged, and plasma was stored at 80C. Before analysis, it was thawed at 4C and protein levels were measured through ELISA. Two-thirds of the patients were females but age distribution across both the groups was not significantly different (p 0.21). No difference was observed in the mean plasma concentrations of AB42, P-Tau, and NFL between the two groups (p-values 0.78 and 0.27 and 0.09 respectively). —Continue